DISTRIBUTION OF PEANUT RECEPTORS TO LECTINS AND CAVIAR PERCH IN THE CAPSULE MEDIASTINAL LYMPH NODE - Васильчук, Н.Г.; Кущ, О.Г. (World of Medicine and Biology, 2015)
According to the results of research lektingistohimicheskih peculiarities of distribution of receptors to lectins peanuts and eggs perch on the capsule mediastinal lymph nodes of white rats in normal conditions and after vnutriplodnoy antigenic load. The tendency to a gradual reduction in the density of peanut lectin receptors on the surface of the capsule lymph nodes under the influence of antigens introduced rat fetus. Regarding the density of receptors for perch roe lectin found the opposite trend.
Keywords: mediastinal lymph node antigen; lectin peanut; lectin perch